The Portrait of Racial Discrimination Against Black American People in Angie Thomas' The Hate U Give - Yanti, Yuliana Indri (Universitas Andalas, 2021)
This research discusses racial discrimination against Black American people represented in the novel The Hate U Give (2017) by Angie Thomas. It aims to analyze how the book reflects racial discrimination in America. This research reveals the impact of racial discrimination, which put black American social into a harmful way, including getting a good education, accessing good work, and getting legal protection. The writer also highlights police brutality that oppresses black American people, which happens because racial bias is rooted in the American police department. The writer applies the sociology of literature propose d by Alan Swingewood and Diana Laurenson, which discusses that literary work represented the social condition when it was produced. The writer also uses a systemic racism theory by Joe R. Feagin to reveal structural racism that oppresses black American people. The analysis shows that black American people find it hard to get equal rights and similar opportunities with other Americans. To get it, Black American people struggle to receive their rights.